Effectiveness of cooperative learning (jigsaw II) method in teaching English as a foreign language to engineering students (Case of Firat University, Turkey) - Gomleksiz, M. N. (Taylor & Francis Ltd, 2007)
The present study compares the effects of the cooperative jigsaw II method and traditional teacher-centred teaching method on improving vocabulary knowledge and active-passive voice in English as a foreign language for engineering students and the students' attitudes towards learning English. Jigsawis a cooperative learning model that involves small groups of 5-6 students teaching each other subject matter with success dependent upon student cooperation. Sixty-six engineering students participated in the study and a pre-test-post-test control group experimental design was employed. The students were randomly assigned into two groups: an experimental group and a control group. The experimental group used cooperative Jigsaw II as an instruction method while the control group used traditional teacher-centred instruction. The groups were administered an achievement test, as a pre-, post-and delayed post-test. The results revealed statistically significant differences in favour of the experimental group on the dependent variables of improving vocabulary knowledge and learning active-passive voice in English. The attitude scale results showed that the cooperative learning experience had a significant positive effect on engineering students' attitudes towards learning English and promoted better interactions among students as well.
Keywords: Engineering education; Cooperative learning; English language teaching; European competitiveness